PENGGUNAAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK PENINGKATAN PEMBELAJARAN PENJUMLAHAN PECAHAN PADA SISWA KELAS V SDN 4 PANDANSARI TAHUN AJARAN 2012/2013 - Permono, Puji (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The use of Model Contextual Teaching and Learning (CTL) for Improved Learning Addition Denomination in Class V Elementary School. The purpose of this study is to describe the implementation of the Contextual Model (CTL) in the improvement of mathematics instruction on the sum of fractions in fifth grade elementary school students and to determine the method of contextual constraints and solutions in improving math learning fractions in the sum Elementary School fifth grade students. This study uses classroom action research. Subjects in this study were fifth grade students of SDN 4 Pandansari who were 30 students consisted of 13 male students and 17 female students. The experiment was conducted in three cycles and each cycle two meetings. The results showed that the use of learning models Contextual Teaching and Learning (CTL), can increase the sum Denomination Learning in Class V. Selection of appropriate learning model is an alternative that can be taken.   Keywords: Models Contextual Teaching and Learning (CTL), Improved Learning, Addition Smithers   Abstrak: Penggunaan Model Contextual Teaching and Learning (CTL) untuk Peningkatan Pembelajaran Penjumlahan Pecahan pada Siswa Kelas V Sekolah Dasar. Tujuan penelitian ini adalah mendeskripsikan pelaksanaan model Kontekstual (CTL) dalam peningkatan pembelajaran matematika tentang penjumlahan pecahan pada siswa kelas V Sekolah Dasar dan untuk mengetahui kendala dan solusi metode Konstekstual dalam peningkatan pembelajaran matematika penjumlahan pecahan pada siswa kelas V Sekolah Dasar. Penelitian ini menggunakan Penelitian Tindakan Kelas. Subjek dalam penelitian ini adalah siswa kelas V SDN 4 Pandansari yang berjumlah 30 siswa terdiri dari 13 siswa laki-laki dan 17 siswa perempuan. Penelitian dilaksanakan  dalam tiga siklus dan masing-masing siklus dua kali pertemuan. Hasilnya menunjukkan bahwa penggunaan model pembelajaran Contextual Teaching and Learning (CTL), dapat meningkatkan Pembelajaran Penjumlahan Pecahan pada Siswa Kelas V. Pemilihan model pembelajaran yang tepat merupakan alternatif yang dapat ditempuh. Kata Kunci: Model Contextual Teaching and Learning (CTL), Peningkatan Pembelajaran, Penjumlahan Pecahan